The Notion of Linguacultureme and Non-Equivalent Lexicon in Different Cultures - qizi, Sharipova Sarvinoz Sayfiddin (Journal of Higher Education and Academic Advancement, 2024)
The article focuses on the notions which have sometimes do not have the alternatives in other languages including linguaculteremes, realia. It takes a close look to the lexicon of several languages and makes some comparisons on the stated notions.